Japanese Firms and the Decision to Invest Abroad: Business Groups and Regional Core Networks - Belderbos, Rene; Sleuwaegen, Leo (The Review of Economics and Statistics, 1996)
The determinants of the decision by Japanese firms to set up manufacturing plants in Southeast Asia, Europe and North America are analyzed using micro-data on the behavior of firms in the electronics industry. While firm-specific intangible assets based on R&D and marketing efforts are positively related to the decision to invest in Europe and North America, investment in Southeast Asia is mainly related to human resources and driven by interfirm ties within horizontal and vertical business groups. The empirical results suggest that membership of horizontal 'keiretsu' relaxes liquidity constraints, while the manufacturing networks of horizontal and vertical 'keiretsu' in Southeast Asia facilitate the establishment of manufacturing plants by member firms. Copyright 1996 by MIT Press.